Reducing the Sink Marks of a Crystalline Polymer Using External Gas-Assisted Injection Molding. (29th February 2020) - Jiang, Shaofei; Li, Taidong; Xia, Xinxin; Peng, Xiang; Li, Jiquan
Abstract : External gas-assisted injection molding (EGAIM) has been used to reduce the sink marks of amorphous polymer products, but that of crystalline polymer products has not yet been reported. EGAIM of a crystalline polymer product was investigated in this study, and the influences of process parameters on the sink marks were discussed based on experiments. An isotactic polypropylene (iPP) product was fabricated by EGAIM under different process conditions. A uniform design was applied as an experimental design to investigate the influences of the process parameters on the sink marks. A regression equation was established to describe the quantitative relationship between the important parameters and sink marks in which a data-processing method was applied to determine the optimal value of F α at significant level α to reduce the possibility of omission of some important parameters. The results show that EGAIM was effective in reducing the sink marks in these iPP products, and the most important parameters were the cooling time, gas pressure, and gas time. This study also provides the quantitative relationship between the important parameters and sink marks as reference for the research of EGAIM on crystalline polymer.